Influence of Supplier Interest on Purchasing Consortia at the County Referral Hospitals in the Coast Region, Kenya - Chebet, Everline; Kitheka, Samson; Hood, Anwar; Kamau, Charles (International Journal of Supply Chain Management, 2024)
Purpose: The objective of the study was to determine the influence of supplier interest on purchasing consortia at the county referral hospitals in the coast region, Kenya. The researcher further investigated the moderating influence of Management Information System on the relationship between supplier interest and purchasing consortia at the county referral hospitals in the coast region, Kenya. Methodology: The study embraced the descriptive research design. The study population comprised of 212 officials drawn from the county referral hospitals in the coast region of Kenya. The stratified random sampling technique used resulted into having 139 units of analysis. The study used primary quantitative data which was collected via questionnaires, whereas data analysis was through the statistical package for social sciences. Findings: The hypothesis testing led to the rejection of H01 since the p-value of .000 was less than .05, thus depicting that supplier interest has a significant positive influence on purchasing consortia at the county referral hospitals in the coast region, Kenya. The hypothesis testing for the moderated relationship model led to the rejection of H02 since the p-value of .000 was less than .05, thus confirming that management information system has a significant positive moderating effect on the relationship between supplier interest and purchasing consortia at the county referral hospitals in the coast region of Kenya. The researcher recommends that county referral hospitals should embrace and consider supplier interest because it influences the purchasing consortia. Unique Contribution to Theory, Practice and Policy: The researcher also recommends that the county referral hospitals should invest in management information system because it has a significant positive moderating effect on the relationship between supplier interest and purchasing consortia at the county referral hospitals in the coastal region of Kenya.